Essentials of intellectual property: law, economics, and strategy - Poltorak, Alexander (Essentials series., 2011)
"The definitive primer on intellectual property for business professionals, non-IP attorneys, entrepreneures, and inventors Full of valuable tips, techniques, illustrative real-world examples, exhibits, and best practices, the Second Edition of this handy and concise paperback will help you stay up to date on the newest thinking, strategies, developments, and caselaw in intellectual property. Presents fundamentals of patents, trademarks, copyrights, trade secrets and other less-know forms of IP, such as registered design and mask works Covers important concepts such as IP strategy, protection, audits, valuation, management, and competitive intelligence Offers an introduction to IP licensing and enforcement Now features discussion of critical precedent-setting recent IP cases and proposed patent reform Providing buiness professionals and IP owners with in-depth knowledge of this extremely important subject, this book helps those new to this field gain a better understanding and appreciation for the results of their creative abilities. "--